A sense of ending. Henry James and Adorno`s "Spätstil" - Gutorow, Jacek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
While we are perfectly justified in acknowledging the emergence of a new idiom in Henry James`s works after 1900 (the date is necessarily tentative), we should see in his so-called late style not only a mere rhetorical or linguistic phenomenon but a result of existential processes transcending questions of style, language and novelistic technique.
Keywords: modernism; aesthetics; late style; organicism; revision